2011
DOI: 10.1128/iai.05451-11
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Alters Effector Functions of Multiple Genes Induced by Borrelia burgdorferi in Macrophages To Regulate Lyme Disease Inflammation

Abstract: Interleukin-10 (IL-10) modulates inflammatory responses elicited in vitro and in vivo by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 99 publications
11
52
0
Order By: Relevance
“…Similar observations have been made in microglial cells, where the pro-or anti-inflammatory states have been elicited by different cytokines or bacterial components (4). In this context, gene expression profiling studies of murine macrophages and microglial cells have identified immunoresponsive gene 1 (Irg1) as one of the most highly up-regulated genes under proinflammatory conditions, such as bacterial infections (5)(6)(7)(8)(9). Increased Irg1 expression levels have also been detected in chicken spleen macrophages after infection with Salmonella enterica (10).…”
mentioning
confidence: 54%
“…Similar observations have been made in microglial cells, where the pro-or anti-inflammatory states have been elicited by different cytokines or bacterial components (4). In this context, gene expression profiling studies of murine macrophages and microglial cells have identified immunoresponsive gene 1 (Irg1) as one of the most highly up-regulated genes under proinflammatory conditions, such as bacterial infections (5)(6)(7)(8)(9). Increased Irg1 expression levels have also been detected in chicken spleen macrophages after infection with Salmonella enterica (10).…”
mentioning
confidence: 54%
“…qRT-PCR was employed to quantify mRNA gene transcripts of various inflammatory genes using the TaqMan Âź RNA-to-C T TM 1-step kit in combination with TaqMan Âź gene expression assays (Applied Biosystems-Life Technologies, Carlsbad, CA, USA) as reported. 38 Amplification of gene transcripts was performed according to the manufacturer's protocol using ABI ViiAℱ 7 real time PCR (Applied Biosystems) and standard amplification conditions. The relative changes in gene expression were calculated using the equation: 2 −ΔΔCT where all values were normalized with respect to the "housekeeping" gene GAPDH (glyceraldehyde 3-phosphate dehydrogenase) mRNA levels.…”
Section: Rna Extraction and Quantitative Real Time Polymerase Chain Rmentioning
confidence: 99%
“…A recent study identified immune response gene 1 (IRG1) as a critical player linking metabolism to innate immunity in oxidative stress response (37). IRG1 was originally identified as a highly inducible gene in murine macrophages following lipopolysaccharide stimulation (38) and is upregulated by proinflammatory cytokines and by viral and bacterial infections (39)(40)(41)(42)(43)(44)(45). The IRG1 gene is highly conserved among different species.…”
mentioning
confidence: 99%